2013
DOI: 10.1369/0022155413517701
|View full text |Cite
|
Sign up to set email alerts
|

Protein Kinase C, Focal Adhesions and the Regulation of Cell Migration

Abstract: Cell adhesion to extracellular matrix is a complex process involving protrusive activity driven by the actin cytoskeleton, engagement of specific receptors, followed by signaling and cytoskeletal organization. Thereafter, contractile and endocytic/recycling activities may facilitate migration and adhesion turnover. Focal adhesions, or focal contacts, are widespread organelles at the cell-matrix interface. They arise as a result of receptor interactions with matrix ligands, together with clustering. Recent anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
60
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(61 citation statements)
references
References 155 publications
1
60
0
Order By: Relevance
“…Cellular attachment to surfaces of culture vessels is maintained by cell-extracellular matrix attachment machinery called focal adhesion [22]; therefore, we examined focal adhesion after GSK-3b inhibition. Immunocytostaining against vinculin revealed that focal adhesion tended to become larger after AR-A0114418 treatment in MDA-MB-231 cells ( Fig.…”
Section: Gsk-3b Inhibition Disturbs the Function Rather Than The Formmentioning
confidence: 99%
See 1 more Smart Citation
“…Cellular attachment to surfaces of culture vessels is maintained by cell-extracellular matrix attachment machinery called focal adhesion [22]; therefore, we examined focal adhesion after GSK-3b inhibition. Immunocytostaining against vinculin revealed that focal adhesion tended to become larger after AR-A0114418 treatment in MDA-MB-231 cells ( Fig.…”
Section: Gsk-3b Inhibition Disturbs the Function Rather Than The Formmentioning
confidence: 99%
“…Focal adhesion tethers the intracellular actin cytoskeleton to the extracellular matrix [22]. We investigated changes in the actin cytoskeleton after treatment with GSK-3b inhibitors.…”
Section: Gsk-3b Inhibition Dysregulates Actin Fibre Organisationmentioning
confidence: 99%
“…The invasion, progression and metastasis of tumor cells was closely related to cell adhesion between the extracellular matrix and other cells [30] . Cell adhesion was dependent on cell adhesion molecules and kinase [31,32] . FAK, a non-receptor binding to tyrosine kinase, which could regulate focal adhesion formation and disassembly, is involved in tumour initiation and progression, including cell survival and apoptosis, adhesion, migration and invasion [33][34][35][36] .…”
Section: Resultsmentioning
confidence: 99%
“…In addition to regulating cytoskeletal organization, Protein Kinase C isoforms are regulators of nuclear segregation[21,39,40]. To determine whether pkcA plays a role during nuclear segregation, we looked at the multinuclearity state of populations of vegetative cells (Fig.…”
Section: Resultsmentioning
confidence: 99%